1995
DOI: 10.3109/03008209509013726
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinctive BMP-Carriers Induce Zonal Chondrogenesis and Membranous Ossification, Respectively; Geometrical Factors of Matrices for Cell-Differentiation

Abstract: A partially purified BMP preparation was combined with a fibrous glass membrane (FGM) or porous particles of hydroxyapatite (PPHAP), and then implanted subcutaneously into the backs of rats. As a control of these new carriers, a conventional carrier of insoluble bone matrix (IBM) was also used. These new geometrically different solid-state carriers induced tissues in quite different manners. FGM/BMP implants induced cartilage formation within the entire inner area of the membrane accompanied by a small amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
88
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 19 publications
9
88
1
Order By: Relevance
“…Biomaterial characteristics, such as porosity, density, and crystallinity, affect the outcome of periodontal regeneration [6][7][8][9][10][11] . Several studies have reported that porous structures enhance bone formation in bone defects [12][13][14][15][16] . Furthermore, it has been shown that pore size has an effect on vascularization 17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterial characteristics, such as porosity, density, and crystallinity, affect the outcome of periodontal regeneration [6][7][8][9][10][11] . Several studies have reported that porous structures enhance bone formation in bone defects [12][13][14][15][16] . Furthermore, it has been shown that pore size has an effect on vascularization 17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…When a ®brous glass membrane is used as a BMP carrier, cartilage formation is induced. Induction of cartilage cells in this system is evidenced by type II collagen synthesis (Kuboki et al, 1995). The ®brous glass implants were removed after 2 weeks and examined by Alcian blue staining and immunohistochemical staining using anti-Maf-1 antiserum.…”
mentioning
confidence: 99%
“…For maf-2, strong mRNA signals were observed in the dorsal and ventral parts of the dorsal horn and a much weaker signal was observed in the Figure 4 Maf expression in BMP implanted tissues. BMP (0.3 mg) was absorbed to a piece of ®brous glass membrane GA-100 (106561 mm, Advantec Co. Tokyo, Japan) and was implanted subcutaneously in the back of rats (Wistar, male, 4 weeks old) as described previously (Kuboki et al, 1995). After 1 or 2 weeks, the implants were removed and subjected to immunohistochemical staining and RNA preparation.…”
mentioning
confidence: 99%
“…The regeneration of lost-parts of the skeleton has been generally carried out with fresh, autogenous bone as a gold standard. To obviate the need for harvesting of grafts and thus, to avoid morbidity resulting from it, the researches for bone substitutes (Kuboki et al, 1995;Asahina et al, 1997;Takaoka et al, 1991;Artzi et al, 2004;Kim et al, 2010) or bone production via bio-engineering have begun (Wozney et al, 1988;Wang et al, 1990;Murata et al, 1999). In the regenerative field, there is a medical need for biomaterials that both allow for bone formation and also gradually absorb as to be replaced by bone.…”
Section: Introductionmentioning
confidence: 99%